Antimicrobial peptides and proteins against drug-resistant pathogens - Yeji Wang; Minghui Song; Wenqiang Chang (The Cell Surface)
The rise of drug-resistant pathogens, driven by the misuse and overuse of antibiotics, has created a formidable challenge for global public health. Antimicrobial peptides and proteins have garnered considerable attention as promising candidates for novel antimicrobial agents. These bioactive molecules, whether derived from natural sources, designed synthetically, or predicted using artificial intelligence, can induce lethal effects on pathogens by targeting key microbial structures or functional components, such as cell membranes, cell walls, biofilms, and intracellular components. Additionally, they may enhance overall immune defenses by modulating innate or adaptive immune responses in the host. Of course, development of antimicrobial peptides and proteins also face some limitations, including high toxicity, lack of selectivity, insufficient stability, and potential immunogenicity. Despite these challenges, they remain a valuable resource in the fight against drug-resistant pathogens. Future research should focus on overcoming these limitations to fully realize the therapeutic potential of antimicrobial peptides in the infection control.